Metode Simple Multi-Attribute Rating Technique (SMART) dan Rank Reciprocal (RR) dalam Penentuan Penerima Beasiswa - Hadad, Sitna Hajar (Journal of Data Science and Information Systems, 2024)
The determination of scholarship recipients is a very important process in supporting the development of individual potential and the empowerment of human resources. This decision not only focuses on academic achievement, but also considers other aspects that reflect leadership values, social contributions, and economic needs. This study aims to apply the SMART method and the Reciprocal Rank weighting method in producing a decision to determine scholarship recipients at SMP XYZ. Weighting using Reciprocal Rank (RR) involves determining the relative weights for each criterion in decision making, and the Simple Multi-Attribute Rating Technique (SMART) can enrich and enhance the assessment process. The final result of ranking scholarship recipients with the integration of the Reciprocal Rank (RR) weighting method and Simple Multi-Attribute Rating Technique (SMART) showed rank 1 with a SMART final score of 0.752 obtained for alternative Student C, 2nd place with a SMART final grade of 0.679 obtained for alternative Student A, 3rd place with a final SMART score of 0.665 obtained for alternative Student B.